2020 IEEE International Reliability Physics Symposium (IRPS) 2020
DOI: 10.1109/irps45951.2020.9128218
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gate Bias on the Anneal of Hot-Carrier Degradation

Abstract: We observe that non-zero gate bias applied during a high temperature anneal following hot-carrier degradation (HCD) impacts degradation recovery in nFETs. The devices are arranged into custom-built arrays and fabricated in a commercial 40 nm bulk CMOS technology and the FET anneal is induced by on-chip poly-Si heaters. The anneal is modeled using Stesmans' passivation model for P b -defects in hydrogen gas (H 2 ). Negative gate bias improves the anneal, in line with studies on biased passivation of process-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The important implication of this research was that the passivation energy of HC-induced defects is not single valued, but follows a Gaussian distribution, caused by the underlying distribution in atomic defect configurations. Furthermore, in our previous work [14], we observed that negative gate bias improves HCD anneal and explained this using the dependence of the passivation of P b -defects on their charge state.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…The important implication of this research was that the passivation energy of HC-induced defects is not single valued, but follows a Gaussian distribution, caused by the underlying distribution in atomic defect configurations. Furthermore, in our previous work [14], we observed that negative gate bias improves HCD anneal and explained this using the dependence of the passivation of P b -defects on their charge state.…”
mentioning
confidence: 59%
“…It is known that in scaled devices the Si-H bond breakage process is more complicated and can consist of a mixture of the multiple particle (MP) process and the single particle (SP) process [21]. In the former, multiple [14] 0.31 [14] 2.56 [24] 0.66 colder carriers collide with the bond and induce its vibrational excitations, increasing its energy. In the latter process, a single highly energetic carrier impinges on the bond and breaks it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations